Targeted Screening of Lactic Acid Bacteria With Antibacterial Activity Toward Staphylococcus aureus Clonal Complex Type 1 Associated With Atopic Dermatitis - Christensen, Ida B.; Vedel, Charlotte; Clausen, Maja-Lisa; Kjærulff, Søren; Agner, Tove; Nielsen, Dennis S. (Frontiers in Microbiology, 2021)
Atopic dermatitis (AD) is a common inflammatory skin disease characterized by an epidermal barrier impairment, as well as a Th2/Th22-skewed immune response, both favoring skin colonization with Staphylococcus aureus. Colonization is strongly related to severity of the disease, and a reduction of S. aureus has been found to alleviate symptoms. Lactic acid bacteria (LAB) produce antimicrobial compounds such as organic acids and bacteriocins and are widely used as probiotics. The aim of this study was to isolate LAB and screen for antibacterial effect specifically toward S. aureus clonal complex type 1. A total of 680 LAB were isolated from fermented vegetables and swab samples from healthy volunteers (vaginal, stool and skin). Screening for antibacterial activity toward S. aureus, narrowed the field of isolates down to four LAB strains with high antibacterial activity. The activity varied according to the specific LAB strain and the origin of the strain. The results suggested different modes of action, including co-aggregation, expression of bacteriocins and production of specific organic acids. However, the ability to acidify the surroundings appeared as the main effect behind inhibition of S. aureus. Broth microdilution assays showed a significant reduction of S. aureus growth when using down to 10% cell free supernatant (CFS). Our results underline the use of specific living LAB or their CFS as potential future treatment strategies to reduce S. aureus colonization of AD skin.